Monitoring and Evaluation of School Finances to Increase Transparency and Accountability - 'Azizah, Nur; Banjarnahor, Lampita; Elfrianto, Elfrianto (Lembaga Riset Mutiara Akbar, 2023)
This research aims to (1) find out how monitoring and evaluation of school finances is carried out; (2) identifying how schools apply the principles of transparency and accountability in managing school finances; (3) Identifying how monitoring and evaluating school finances has an impact on improving school financial management. For the successful implementation of education, one element of school financial management is managing and making the best use of financial management. Schools need to carry out good school financial management by planning and developing all the resources they have effectively and efficiently. This research approach uses qualitative methods and data collection techniques are carried out through interviews, observation and document research. The target of this research is school treasurers who have an important role in managing school finances. The research results show that the implementation of financial monitoring and evaluation was successful and was carried out directly by the school principal and school authorities. When monitoring and evaluating school finances, minimal deviations were found in the RKAS that had been prepared. Monitoring and evaluation practices aim to increase transparency and accountability in school financial management and prevent undesirable things from happening